Urban tour tet’s Urban talk; Guidelines for tourism promotion by cultural heritage on Urban landscape in Roi Et province, Thailand - WACHIRAYA TATIYANANTAKUL (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: The goals of this research are to (a) investigate the factors that shape Roi-Et Province’s most significant urban landscapes, (b) assess how these urban landscapes influence the province’s tourism industry, and (c) propose strategies for boosting the province’s tourism industry through the use of cultural heritages.Methodology: Data about the city’s fundamental components that impact tourism were collected, recorded, and their significance was determined with the help of an observation form.Findings: Path, edge, node, districts, and landmark are five of the most fundamental components of the Roi-Et urban landscape. I also looked into Roi-historical Et’s significance.Novelty/Implications: The knowledge management of cultural resources maximizes benefits, and this study analyzed the value and significance of Roi-cultural Et’s heritage in the urban landscape. It was found that the value and significance of cultural heritage vary greatly from one area to the next.